The Decline of Magic: Britain in the Enlightenment by Michael Hunter - Gauld, Alan (Journal of Scientific Exploration, 2020)
In the preface to this very Scholarly – and sometimes almost confusingly well-informed - book the author tells us that his aim is to offer “a fresh view of the change in educated attitudes towards magical beliefs that occurred in Britain between about 1650 and 1750.” In this he unquestionably succeeds. Actually the book continues somewhat beyond the later date, but there can be no doubt that there were changes – mostly declines - during the designated period in many of the miscellaneous human beliefs and activities that have for whatever reason been labelled as ‘magic’ or ‘magical’. Hunter begins the body of his book with a chapter–length Introduction entitled The Supernatural, Science and ‘Atheism’. This opens with an attempt to define what he means by ‘magic’, based, he says, on the similar attempt made by Sir Keith Thomas in his classic Religion and the Decline of Magic (1971), though unlike Thomas he very wisely does not include alchemy and astrology. Even so he includes quite a wide variety of topics, so wide indeed that it is hard to see what if anything these phenomena – if they do indeed occur – could have in common except that they are difficult to explain, or to explain away, in ordinarily accepted terms. The proposed list includes such matters as witchcraft, witch covens, involvement with the spiritual realm (good or evil, angelic or demonic, benevolent or pestilential) possession. conjuration, prophesies, ghosts, apparitions, fairies, omens and lucky charms, and what would now be called poltergeists. Other varieties of curious events linked to or supposedly similar to the above could in practice no doubt get included.